EN FACE IMAGE–BASED ANALYSIS OF RETINAL TRACTION CAUSED BY EPIRETINAL MEMBRANE AND ITS RELATIONSHIP WITH VISUAL FUNCTIONS. Issue 7 (July 2020) - Hirano, Masayuki; Morizane, Yuki; Kanzaki, Yuki; Kimura, Shuhei; Hosokawa, Mio; Shiode, Yusuke; Doi, Shinichiro; Toshima, Shinji; Takahashi, Kosuke; Hosogi, Mika; Fujiwara, Atsushi; Takasu, Ippei; et al.
Abstract : Purpose: To evaluate the relationship between retinal traction caused by epiretinal membrane and visual functions. Methods: In this institutional study, en face swept-source optical coherence tomography images of 141 eyes of 130 patients with epiretinal membrane were analyzed to investigate maximum depth of retinal folds, which represents retinal traction strength and the distribution pattern of retinal folds. We investigated the relationships between the maximum depth and distribution pattern of retinal folds and visual functions as well as the effects of membrane peeling. Results: Maximum retinal fold depth was significantly correlated with the metamorphopsia score ( P < 0.001). Fifteen eyes showed retinal folds radially extending from the macular epiretinal membrane (radiating folds group), whereas 126 eyes showed a multidirectional pattern of retinal folds (multidirectional folds group). The radiating folds group showed a significantly lower metamorphopsia score ( P = 0.014). Multiple regression analysis revealed that the metamorphopsia score was significantly related to maximum retinal fold depth ( P = 0.003), distribution pattern ( P = 0.015), and central retinal thickness ( P < 0.001). One month after membrane peeling, parafoveal retinal folds resolved completely in all cases, and both visual acuity ( P < 0.001) and average metamorphopsia score ( P = 0.036) were significantly improved. Conclusion: Both the strength and the distribution pattern of retinal traction are significantly related to metamorphopsia in epiretinal membrane patients. Abstract : Supplemental Digital Content is Available in the Text.We visualized retinal folds caused by epiretinal membrane using en face images taken with swept-source optical coherence tomography and investigated the relationship between retinal traction and visual functions. Our results indicate that both the strength and the distribution pattern of retinal traction are important for visual functions.